Sleep-wake patterns of fencing athletes: a long-term wearable device study - Jiansong Dai; Xiaofeng Xu; Gangrui Chen; Jiale Lv; Yang Xiao (PeerJ)
Objective Sleep is the most efficient means of recovery for athletes, guaranteeing optimal athletic performance. However, many athletes frequently experience sleep problems. Our study aims to describe the sleep-wake patterns of fencing athletes and determine whether factors, such as sex, competitive level and training schedules, could affect the sleep-wake rhythm. Methods Sleep data from 23 fencing athletes were collected using the Huawei Band 6, monitoring key sleep parameters such as bedtime, wake time, duration of deep and light sleep, wake periods, REM sleep duration, and nap duration. During this period, athletes were required to wear the band continuously for 24 hours daily, except bathing, charging, and competition times. Results Athletes averaged 7.97 hours of sleep per night, with significant differences observed in wake time (p = 0.015) and midpoint of sleep (p = 0.048) between high-level and low-level athletes, as well as a higher frequency of naps among high-level (χ2 = 11.97, p = 0.001) and female (χ2 = 3.88, p = 0.049) athletes. Nap duration was negatively correlated with night sleep duration (r =  − 0.270, p < 0.001). Athletes were observed for changes in sleep-wake patterns from Monday to Sunday. On Mondays, Wednesdays, and Fridays, when there was no morning training, the athletes’ wake-up time and the midpoint of sleep were shifted significantly backward, and there were significant differences in sleep parameters between training days and rest days. Conclusion The sleep patterns of athletes differ according to level and gender. The sleep-wake patterns of athletes are influenced by training schedules, indicating the presence of sleep rhythm disruption.